1995
DOI: 10.1083/jcb.130.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate inhibits PDGF-induced chemotaxis of human arterial smooth muscle cells: spatial and temporal modulation of PDGF chemotactic signal transduction.

Abstract: Abstract. Activation of the PDGF receptor on human arterial smooth muscle cells (SMC) induces migration and proliferation via separable signal transduction pathways. Sphingosine-l-phosphate (Sph-l-P) can be formed following PDGF receptor activation and therefore may be implicated in PDGF-receptor signal transduction. Here we show that Sph-l-P does not significantly affect PDGF-induced DNA synthesis, proliferation, or activation of mitogenic signal transduction pathways, such as the mitogen-activated protein (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
185
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(197 citation statements)
references
References 53 publications
(59 reference statements)
11
185
1
Order By: Relevance
“…In addition, it was shown that sphingosine, a precursor of S1P, could alter cellular PAK activity (11) and PDK1 activity (33). It was also noted that higher concentrations of S1P are required for inhibition of cell motility in breast cancer cells (72,74) than in vascular smooth muscle cells (12) and B16 melanoma cells (59,77). Moreover, dihydro-S1P, an agonist for the EDG S1P receptors (70,71), is ineffective in inhibiting the motility of the breast cancer cells (74), which contrasts with the present data for CHO-EDG5 cells (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it was shown that sphingosine, a precursor of S1P, could alter cellular PAK activity (11) and PDK1 activity (33). It was also noted that higher concentrations of S1P are required for inhibition of cell motility in breast cancer cells (72,74) than in vascular smooth muscle cells (12) and B16 melanoma cells (59,77). Moreover, dihydro-S1P, an agonist for the EDG S1P receptors (70,71), is ineffective in inhibiting the motility of the breast cancer cells (74), which contrasts with the present data for CHO-EDG5 cells (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular mechanisms by which the chemorepellants suppress cell migration have remained largely unknown. S1P is unique and distinct from these chemorepellants in that it bidirectionally regulates cell migration, i.e., S1P acts as a chemoattractant for certain cell types (34,40,41,73), while it strongly inhibits cell migration in others (12,31,59,72,77); the latter include several tumorderived cell types. S1P is a normal constituent of the blood and is present at a substantially high concentration (Ͼ0.1 M), most of which is bound to albumin (79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…98 The finding that sphingosine-1-phosphate may be an inhibitor of plateletderived growth factor-induced migration of ASMCs is of considerable significance. 74,75 In addition, the protective role of trimethylsphingosine of the myocardium and endothelium in ischemia/reperfusion injury has been suggested. 71 Several mechanisms have been implicated in the initiation of early atherogenesis.…”
Section: Functional Role Of Sphingolipids In Vascular Cell Biology Anmentioning
confidence: 99%